Nanoscopic surfactant behavior of the porin MspA in aqueous media - Perera, Ayomi S.; Wang, Hongwang; Shrestha, Tej Bahadur; Troyer, Deryl L.; Bossmann, Stefan H. (My University, 2013)
The mycobacterial porin MspA is one of the most stable channel proteins known to date. MspA forms vesicles at low concentrations in aqueous buffers. Evidence from dynamic light scattering, transmission electron microscopy and zeta-potential measurements by electrophoretic light scattering indicate that MspA behaves like a nanoscale surfactant. The extreme thermostability of MspA allows these investigations to be carried out at temperatures as high as 343 K, at which most other proteins would quickly denature. The principles of vesicle formation of MspA as a function of temperature and the underlying thermodynamic factors are discussed here. The results obtained provide crucial evidence in support of the hypothesis that, during vesicle formation, nanoscopic surfactant molecules, such as MspA, deviate from the principles underlined in classical surface chemistry.
Keywords: Charge-interaction; Hydrophobic interaction; Liposome-type cluster; Protein cluster; Temperature influence; Zeta potential